anonymous
  • anonymous
Apply the distributive formula to (x+y)^2 = x^2 + 2xy + y^2
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
xapproachesinfinity
  • xapproachesinfinity
first do this \((x+y)^2=(x+y)(x+y)\)
xapproachesinfinity
  • xapproachesinfinity
now try to distribute
anonymous
  • anonymous
|dw:1439924847191:dw|

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
(x+y) (x+y) = (x^2 + xy + xy + y^2) @xapproachesinfinity @Crazyandbeautiful
anonymous
  • anonymous
combine like terms, you have the right hand side
anonymous
  • anonymous
so i just combine all thats on the left now?
anonymous
  • anonymous
@Crazyandbeautiful x^2+xy+xy+y^2 = (x^2 + xy + xy + y^2)
anonymous
  • anonymous
@Crazyandbeautiful @xapproachesinfinity is this right???
anonymous
  • anonymous
\[xy+xy=2xy\] Just like how \[a+a=2a\]
anonymous
  • anonymous
do you understand that @The_Yee_Dinosaur
anonymous
  • anonymous
yea
anonymous
  • anonymous
but it is not a true equation now such as 25=25 or 17=17 right? @Crazyandbeautiful
anonymous
  • anonymous
@Nishant_Garg
anonymous
  • anonymous
It is true, an equation is what an equation is, the left side is equal to the right side try it for your self take an example \[(3+4)^2\] Let's solve it directly and using the identity Directly first \[(3+4)^2=7^2=49\] Now we apply the identity \[(3+4)^2=3^2+4^2+2(3)(4)=9+16+24=49\]
anonymous
  • anonymous
Think of it like this, x and y are numbers so if you multiply x and y, that is calculate \[xy\](the product of x and y) you will get another number) now suppose you add that same final number you got that itself what do you get? It's 2 times the number itself Math will work whether you take letters or numbers
anonymous
  • anonymous
Suppose x=3 and y=4 \[xy=3\times4=12\] \[12+12=24=2 \times 12\] \[xy+xy=2xy=2 \times xy\]
phi
  • phi
they may want you do use the distributive property twice \[ (x+y)(x+y) \] if we call the first (x+y) "A" (to make it clearer) we would do this (distribute) \[ A (x+y) = Ax + Ay \] and A is really (x+y), so this is \[ (x+y)(x+y)=(x+y)x + (x+y)y \] now distribute again. in other words the first (x+y)x becomes x^2 +xy and the second term becomes xy+y^2 \[ (x+y)x + (x+y)y = x^2 +xy+xy+y^2 \] finally , add xy+xy (1 xy plus another xy is 2xy) \[ (x+y)(x+y)= x62+2xy+y^2 \]

Looking for something else?

Not the answer you are looking for? Search for more explanations.